Robust Password Encryption Technique with an Extra Security Layer - Abdulla, Qusay Zuhair; Al-Hassani, Mustafa Dhiaa (Iraqi Journal of Science, 2023)
People are comfortable with e-banking services, but they are exposed to a great deal of danger these days due to fraudulent acts such as password hacking and personal information theft. Everything individuals do online relies heavily on passwords. Using a password protects one's identity online, in forums, and through email. Online transactions are vulnerable to identity theft if they do not have a secure password. Internet users with critical statements are vulnerable to various assaults, including the theft and exploitation of user IDs and passwords. This paper introduces novel password encryption by fingerprint and a random number to make each password unique and robust against attacks, with a magnificent time elapsed of under 40 milliseconds. This paper uses global password datasets with different stages of password complexity. This method protects the bank’s clients' password accounts inside the bank database.